Susceptibility loci of CNOT6 in the general mRNA degradation pathway and lung cancer risk—A re‐analysis of eight GWASs. Issue 4 (15th November 2016) - Zhou, Fei; Wang, Yanru; Liu, Hongliang; Ready, Neal; Han, Younghun; Hung, Rayjean J.; Brhane, Yonathan; McLaughlin, John; Brennan, Paul; Bickeböller, Heike; Rosenberger, Albert; Houlston, Richard S.; et al.
Abstract : Purpose: mRNA degradation is an important regulatory step for controlling gene expression and cell functions. Genetic abnormalities involved in mRNA degradation genes were found to be associated with cancer risks. Therefore, we systematically investigated the roles of genetic variants in the general mRNA degradation pathway in lung cancer risk. Experimental design: Meta‐analyses were conducted using summary data from six lung cancer genome‐wide association studies (GWASs) from the Transdisciplinary Research in Cancer of the Lung and additional two GWASs from Harvard University and deCODE in the International Lung Cancer Consortium. Expression quantitative trait loci analysis (eQTL) was used for in silico functional validation of the identified significant susceptibility loci. Results: This pathway‐based analysis included 6816 single nucleotide polymorphisms (SNP) in 68 genes in 14 463 lung cancer cases and 44 188 controls. In the single‐locus analysis, we found that 20 SNPs were associated with lung cancer risk with a false discovery rate threshold of <0.05. Among the 11 newly identified SNPs in CNOT6, which were in high linkage disequilibrium, the rs2453176 with a RegulomDB score "1f" was chosen as the tagSNP for further analysis. We found that the rs2453176 T allele was significantly associated with lung cancer risk (odds ratio = 1.11, 95% confidence interval = 1.04–1.18) in the eight GWASs. In the eQTL analysis, we found that levels of CNOT6 mRNA expression were significantly correlated with the rs2453176 T allele, which provided additional biological basis for the observed positive association. Conclusion: The CNOT6 rs2453176 SNP may be a new functional susceptible locus for lung cancer risk. © 2016 Wiley Periodicals, Inc.